2018
DOI: 10.1101/298364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep mutational scanning of hemagglutinin helps predict evolutionary fates of human H3N2 influenza variants

Abstract: Human influenza virus rapidly accumulates mutations in its major surface protein hemagglutinin (HA). The evolutionary success of influenza virus lineages depends on how these mutations affect HA's functionality and antigenicity. Here we experimentally measure the effects on viral growth in cell culture of all single amino-acid mutations to the HA from a recent human H3N2 influenza virus strain. We show that mutations that are measured to be more favorable for viral growth are enriched in evolutionarily success… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(98 citation statements)
references
References 98 publications
(131 reference statements)
5
93
0
Order By: Relevance
“…We used the Lumière implementation of the MFBD model to estimate the fitness effects of amino acid mutations in the hemagglutinin (HA) protein of human influenza virus subtype H3N2. In order to ensure our fitness estimates were directly comparable to the mutational fitness effects previously estimated by Lee et al [2018], we focused our analysis on viral samples in the same antigenic cluster as the A/Perth/16/2009 strain studied by Lee et al for two reasons. First, Lee et al [2018] showed that the fitness effects of amino acid mutations in HA vary depending on the genetic background, with greater fitness differences between more divergent strains.…”
Section: Influenza H3n2 Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We used the Lumière implementation of the MFBD model to estimate the fitness effects of amino acid mutations in the hemagglutinin (HA) protein of human influenza virus subtype H3N2. In order to ensure our fitness estimates were directly comparable to the mutational fitness effects previously estimated by Lee et al [2018], we focused our analysis on viral samples in the same antigenic cluster as the A/Perth/16/2009 strain studied by Lee et al for two reasons. First, Lee et al [2018] showed that the fitness effects of amino acid mutations in HA vary depending on the genetic background, with greater fitness differences between more divergent strains.…”
Section: Influenza H3n2 Analysismentioning
confidence: 99%
“…In order to ensure our fitness estimates were directly comparable to the mutational fitness effects previously estimated by Lee et al [2018], we focused our analysis on viral samples in the same antigenic cluster as the A/Perth/16/2009 strain studied by Lee et al for two reasons. First, Lee et al [2018] showed that the fitness effects of amino acid mutations in HA vary depending on the genetic background, with greater fitness differences between more divergent strains. We therefore only considered strains with low genetic divergence from A/Perth/16/2009.…”
Section: Influenza H3n2 Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent approach combines mutagenesis by PCR with degenerate (NNK) primers with in-cell recombination to create variation at specific residues in the tail fiber of T3 phage (Yehl et al 2019). By contrast, human viruses often have reverse genetics systems in place where comprehensive mutant libraries can be prepared for single genes or regions within a gene (Doud et al 2018, Wu andQi 2019) using replicative plasmids that encode whole viruses or viral components. Similarly, deep mutational scanning can be performed on plasmid-encoded phage proteins like the MS2 capsid protein (Hartman et al 2018).…”
Section: Introductionmentioning
confidence: 99%